Long-term care for aged ethnic minority people in Yunnan, China: Understanding the situation. Issue 3 (1st July 2016) - Zhang, Kaining; Zakus, David; Gao, Chuqun
Abstract : Chinese governmental sectors have been investing lots of money in setting up new institutions for long-term care (LTC) in rural China to respond to the predicted increasing and urgent needs of the growing number of aging people. However, very few have identified that many ethnic minority groups have been enjoying their traditional home-based LTC systems, which are cost-effective and have been working really well for generations. This article reports on a study on LTC needs and provisions for the Dai, one of the ethnic minority groups in rural areas of southwest China, in Yunnan (Province). A randomized sample was drawn from 12 villages in Ruili, a county 752 km from Kunming, the capital city of Yunnan. Totally, 187 elderly persons were interviewed intensively. Activities of daily living were measured as the core indicator for understanding LTC. The research revealed that there is a significant disparity between the needs of the villagers and provisions from the different levels of government. There is an urgent need to reexamine the allocation of public resources for the aged. Traditional culture and practices of caring for the elderly, and practices in LTC of different ethnic groups, must be carefully considered.